Pengaruh Sekularisasi dalam Diskursus Worldview Barat: The Influence of Secularization in the Discourse of the Western Worldview - Syamsuddin Arif; Fasya Tharra Annada; Haqiqul Rezkyanta (Center of Islamic and Occidental Studies, 2025)
The study of worldview in the West has developed since the end of 18th century. Western scholars have each provided their own definitions of worldview. Therefore, this research aims to analyze the influence of secularization on the discourse of worldview in the West by employing a qualitative approach and content analysis method. The findings show that the modern Western worldview is based on human reason and culture, and only affirms what is empirical. Consequently, the Western worldview marginalizes God and religion, as well as denies non-empirical realities. This is the result of secularization, which separates worldly affairs from religion. In contrast, the worldview of Islam is centered on God and religion, and perceives reality as a whole—embracing both the empirical and the non-empirical.